EFFECTS OF EXPERIMENTAL METHODOLOGY AIMED AT INCREASING THE FORCE OF STRAIGHT REAR-HAND PUNCH IN KARATE - Radoslav Penov; Milen Chalakov (Journal of Applied Sports Sciences)
This article presents a methodology aimed at increasing the force of the rear-hand straight punch at the torso-level (gyaku zuki chudan). To accomplish the tasks of the survey, a video-computerized system was used to record and analyze the parameters of the punches performed by the participants. The results concerning the force of the torso-level rear-hand straight punch were registered in identical ways for each of the participants in order to make sure that the survey was performed under uniform conditions. The input data was processed by means of kinematics analysis software. To prove the credibility of the data registered the necessary statistical analysis methods were applied. If more and more coaches start using modern tools and methods to develop the sports and technical skills of their entrusted athletes, this will increase the quality of the karate training process.